Metabarcoding data reveal vertical multitaxa variation in topsoil communities during the colonization of deglaciated forelands - Alessia Guerrieri; Alexis Carteron; Aurélie Bonin; Silvio Marta; Roberto Ambrosini; Marco Caccianiga; Isabel Cantera; Chiara Compostella; Guglielmina Diolaiuti; Diego Fontaneto; Ludovic Gielly; Fabrizio Gili; et al. (Molecular Ecology, 2023)
Ice‐free areas are expanding worldwide due to dramatic glacier shrinkage and are undergoing rapid colonization by multiple lifeforms, thus representing key environments to study ecosystem development. It has been proposed that the colonization dynamics of deglaciated terrains is different between surface and deep soils but that the heterogeneity between communities inhabiting surface and deep soils decreases through time. Nevertheless, tests of this hypothesis remain scarce, and it is unclear whether patterns are consistent among different taxonomic groups. Here, we used environmental DNA metabarcoding to test whether community diversity and composition of six groups (Eukaryota, Bacteria, Mycota, Collembola, Insecta, and Oligochaeta) differ between the surface (0–5 cm) and deeper (7.5–20 cm) soil at different stages of development and across five Alpine glaciers. Taxonomic diversity increased with time since glacier retreat and with soil evolution. The pattern was consistent across groups and soil depths. For Eukaryota and Mycota, alpha‐diversity was highest at the surface. Time since glacier retreat explained more variation of community composition than depth. Beta‐diversity between surface and deep layers decreased with time since glacier retreat, supporting the hypothesis that the first 20 cm of soil tends to homogenize through time. Several molecular operational taxonomic units of bacteria and fungi were significant indicators of specific depths and/or soil development stages, confirming the strong functional variation of microbial communities through time and depth. The complexity of community patterns highlights the importance of integrating information from multiple taxonomic groups to unravel community variation in response to ongoing global changes.